Pojok Literasi sebagai Upaya Meningkatkan Minat Baca Anak Usia 5-6 Tahun Di Tk Kartika IX-24 Salatiga - Sriwijayati, Indar; Kurnia Putri, Meylisia; Puspitasari, Rina; Za'im Luthfya, Ulya; Hidayah, Wahidatul (Program Studi S1 PG-PAUD, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Satya Wacana, 2024)
Literacy corner or commonly called reading corner is the utilization of classroom corner as an extension of library, which is attempted to increase children’s interest in reading. Increasing children’s interest in reading will impact various aspects of their growth and development especially in terms of language. In early childhood, increasing interest reading will be an efforts to prepare students for further education. The purpose of this study was to find out how reading corner affects increasing children’s interest in reading aged 5-6 years, and how reading corner is implemented to increase children’s interest in reading aged 5-6 years. The method used in this study is descriptive qualitative, data collection was conducted through observation and documentation conducted on children in group B of one of the kindergartens in Salatiga. The results of the analysis showed an increase in children’s interest in reading with the existence of literacy corner which was designed with effective program and attractive arrangement for students. From the first week of the study showed the number of visitors of group B was 7 students, it appeared in the fourth week it increased to 21 students who visited and utilized literacy corner. Therefore, literacy corner is very effective to be used as a means to increase children’s interest in reading aged 5-6 years.